Identification of misconceptions in plant morphology using a four-tier diagnostic test - Zahwa Fibrianita; Wisanti Wisanti; Siti Zubaidah (Journal of Educational and Learning Studies, 2026)
This study aims to identify and map the highest levels of misconceptions regarding plant morphology among Grade 11 high school students in Surabaya. A descriptive survey involved 114 11th-grade students from nine high schools in Surabaya, selected through random sampling. Based on answer accuracy, reasoning accuracy, and confidence levels, students’ responses were classified into conceptual understanding, partial understanding, lack of conceptual understanding, and misconception categories. Data were collected using the Four-Tier Diagnostic Test on Plant Morphology (MorforTest), consisting of 10 items. The instrument was validated by four biology experts and obtained a validity score of 90% (highly valid) and Cronbach alpha reliability  score  of  0.75  (reliable). Data were analyzed descriptively using percentages. The findings indicated that students exhibited misconceptions in the low (55%), moderate (40%), and high (5%) categories. The highest misconception rates were found in the concepts of Asteraceae inflorescences (45%) and the lamina and stamens of Canna indica (44%), whereas the lowest misconception rate was observed for moss rhizoids (14%). Thus, MorforTest can be recommended as a diagnostic tool to help teachers design learning strategies that minimize misconceptions in plant morphology.